Reversible interventions for menstrual management in adolescents and young adults with gender incongruence - Rosemary Claire Roden (Therapeutic Advances in Reproductive Health, 2023)
The newly released World Professional Association for Transgender Health Standards of Care, 8th Edition specify that adolescents should be offered menstrual suppression as part of their treatment plans to suppress menses and alleviate dysphoria, provide contraception, or improve irregular bleeding on testosterone therapy. This is a review of current evidence-based options for reversible interventions for menstrual suppression in adolescents with gender dysphoria or incongruence. Shared decision-making should be used by the clinician at all times, and the clinician should be intentional in prioritizing the patient’s stated needs and desires when offering interventions. No method should be withheld due to the experience of gender incongruence alone. Contraceptive options offering menstrual suppression include depot-medroxyprogesterone acetate, levonorgestrel intrauterine systems, progestin-only contraceptive pills, and combined hormonal contraceptives. Non-contraceptive options include norethindrone acetate, oral medroxyprogesterone acetate, gonadotropin-releasing hormone analogues/agonists, and danazol. Certain patients may also benefit from non-pharmacologic interventions, such as specialty menstrual underwear. Plain language summary Using medicine to stop Menstrual periods in teens with gender incongruence Summary: Newly released recommendations for the care of teens and young adults with gender dysphoria or incongruence specifically recommend using medications to get rid of menstrual periods if desired or medically necessary. Patients may ask for this to help improve dysphoria, as a feature they want in birth control, or simply because they do not want to have periods. Because temporarily getting rid of periods is something that doctors can do for any patient old enough to have periods, patients with gender dysphoria should also be able to have their periods temporarily stopped using medications if requested. Doctors should ensure that they always help the patient make a decision that is right for them instead of prescribing what they think is right without considering the patient’s input. Options for temporarily getting rid of periods can include birth control, such as oral contraceptive pills, patches, or rings; intrauterine devices; or shots, and it can also be done with things that are not birth control, such a progesterone pills or puberty blockers. Finally, some patients may only need improved period hygiene with period underwear to feel better in their bodies.